2014
DOI: 10.1371/journal.pone.0107506
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Lung Sound Distribution and Pulmonary Function in COPD Patients

Abstract: BackgroundRegional lung sound intensity in chronic obstructive pulmonary disease (COPD) patients is influenced by the severity and distribution of emphysema, obstructed peripheral airways, and altered ribcage and diaphragm configurations and movements due to hyperinflation. Changes in the lung sound distribution accompanied by pulmonary function improvements in COPD patients were observed after bronchodilator inhalation. We investigated the association of lung sound distribution with pulmonary functions, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Significant and lower correlations were also found between FEV 1 %predicted and Imax at the anterior chest. Similar results have been reported and might be related with a shift of regional ventilation from the lower‐ to upper‐lung locations as a function of the degree of hyperinflation presented in more severe COPD patients. This type of hyperinflation can be reversed with therapy and inspiratory maximum intensity recorded at the anterior chest may be an adequate outcome measure to assess these changes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Significant and lower correlations were also found between FEV 1 %predicted and Imax at the anterior chest. Similar results have been reported and might be related with a shift of regional ventilation from the lower‐ to upper‐lung locations as a function of the degree of hyperinflation presented in more severe COPD patients. This type of hyperinflation can be reversed with therapy and inspiratory maximum intensity recorded at the anterior chest may be an adequate outcome measure to assess these changes.…”
Section: Discussionsupporting
confidence: 88%
“…Significant and lower correlations were also found between FEV 1 %predicted and Imax at the anterior chest. Similar results have been reported 40 and might be related FIGU RE 1 Bland and Altman plots of number of crackles and wheeze occupation rate (%Wh) collected at session 1 (S1) and session 2 (S2) at posterior right and left chest. Solid lines represent the zero value, and dashed lines show the associated bias and 95% upper limit of agreement (ULA) and lower limit of agreement (LLA) FIGU RE 2 Bland and Altman plots of median frequency (F50) and maximum intensity (Imax) collected at session 1 (S1) and session 2 (S2) at posterior right and left chest.…”
Section: Discussionsupporting
confidence: 85%
“…Although positive correlation can be identified through acoustic imaging and lung disorders, chronic respiratory diseases, such as asthma and COPD, have not been correlated positively [5], [22]. Moreover, the correlation between acoustic sensors placement and sensitivity were not investigated, and the position of the sensors was typically empirical [5], [11], [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the obstructive lung disease is a common comorbidity among patients undergoing thoracic surgery and accordingly we observed that a considerable number of participants (20%) had obstructive pulmonary disease in the present study. The intensity and distribution of lung sounds are profound altered in patients with obstructive lung disease ( 27 ) and this may hamper correct auscultation. Nevertheles,.…”
Section: Discussionmentioning
confidence: 99%